Islamic values on ISO 9001-2000 certified companies in Malaysia - Shuriye, Abdi Omar; Che Daud, Mohd Radzi; Mat Song, Rusdi; Ismail, Mohd Azhar (Islamic Centre for Education, Research and Development, 2009)
ISO 9001: 2000 is the level of quality that all organizations or companies should have. This level of quality has been setup by the International Organization for Standardization (ISO). ISO 9001:2000 is an international standard containing requirements for establishing and maintaining company’s quality management system. This quality management system is set up by a company to establish a quality policy and quality objectives, and to establish the means to achieve those objectives. This standard is very general and universal. It can be applied from product manufacturers to service providers. This ISO 9001 is divided into four main sections; (i) management responsibility, (ii) resource management, (iii) product realization, and (iv) measurement, analysis and improvement. Although ISO has underlined a clauses that must be fulfilled to achieve the ISO 9001:2000 certification, we felt that ISO certification is not sufficient in developing and establishing values. We could say that the certification of the ISO 9001:2000 is somehow neglecting and lack of moral and spiritual values. This is because through this certification people tend to work on the bases of producing and supplying the customer the best quality products and at the same time neglecting the values that one must have. In recent years, there are numerous of management theories, techniques, approaches or styles which have been claimed to contribute towards “improved quality”, “excellence”, “creating a difference”, “creating a niche”, “increasing competitiveness”, etc. which are all aimed at having the competitive edge over the competitors to survive or to be ahead of them. The problems are, with such of these values, people tend to ignored one another, people tend not to be with their families for quite a long time, people tend to be insincere with each other and most of all, people tend to work hard and ignored their Creator. In short, by working hard, people tend to forget about themselves and much, they forget their moral and spiritual values. This is because societies have affective regard for certain values for some reason which may only be contemporary in nature. Recently research has witnessed the demise of Communism in Europe with consequential economic backwardness, political instability and social disorder. Even though Japan has succeeded as the most developed country in Asia, statistic showed that their people tend to commit suicide each day due to the pressure of working. Times are witnessing the gradual decline of the U.S and Japanese economies which are still mimicking industrialization, modernization and secularization of the west. These declines are due to the moral decadence of modern societies.